Underestimated self-perception of stepping-forward decreases the risk of falls in community dwelling older adults. - Bravo, Jorge (2020)
The impact and the high costs that falls represent for older adults, family, social, health and economic community, are a constant concern such as respect for the human imension and the fight against social exclusion. The priority of social projects and agents is to identify risk factors in order to prevent falls and to guarantee an aging without fear, without injury, without disabilities and without social dependence. The present study aimed to analyse the role of the estimated and the real stepping- forward (SF) in the prevalence of falls in older adults from Alentejo region, Portugal.